2015
DOI: 10.21102/gefj.2015.09.82.06
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Market Reaction to Right Share Offers in Bangladesh

Abstract: We have examined the right offers made between January 2010 to October 2012 by companies listed on the Dhaka Stock Exchange and tested the speed of adjustment of market price of the issuers to the right issues. The analysis leads to the conclusion that the adjustment is not immediate, the market price is about 10-11 percent higher than the right adjusted price on the average and the difference is statistically significant. It takes about 15 days for the market price to reach a stage where the difference betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In one of the recent studies, Ahkam and Mostafa (2013) examined the companies listed at DSE and tested the speed of adjustment of market prices to released information.They found that the adjustment is not immediate, and it takes about 15 days for the market to fully absorb and reflect such information. Understanding the anomalies and inconsistencies is essential to map out proper policy prescriptions.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…In one of the recent studies, Ahkam and Mostafa (2013) examined the companies listed at DSE and tested the speed of adjustment of market prices to released information.They found that the adjustment is not immediate, and it takes about 15 days for the market to fully absorb and reflect such information. Understanding the anomalies and inconsistencies is essential to map out proper policy prescriptions.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%